2014
DOI: 10.1638/1042-7260-45.2.263
|View full text |Cite
|
Sign up to set email alerts
|

PULMONARY DEAD SPACE IN FREE-RANGING IMMOBILIZED BLACK RHINOCEROSES (DICEROS BICORNIS) IN NAMIBIA

Abstract: It was observed previously that end-expired carbon dioxide (P(E)CO2) decreased when immobilized black rhinoceroses (Diceros bicornis) were moved from sternal to lateral recumbency. These experiments were designed to test whether greater alveolar ventilation or greater pulmonary dead space in lateral recumbency explains this postural difference in P(E)CO2. Twenty-one (9 male, 12 female; 15 [3.5-26] yr old) wild black rhinoceroses were immobilized with etorphine and azaperone and positioned in either sternal or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 18 publications
2
6
0
Order By: Relevance
“…Immobilization with etorphine-medetomidine-midazolam resulted in short induction times similar to those previously reported in free-ranging black rhinoceroses immobilized with other etorphine-combinations ( 6 , 8 , 9 ) and uneventful recoveries. No muscle tremors were observed and lac was normal in all but one animals.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Immobilization with etorphine-medetomidine-midazolam resulted in short induction times similar to those previously reported in free-ranging black rhinoceroses immobilized with other etorphine-combinations ( 6 , 8 , 9 ) and uneventful recoveries. No muscle tremors were observed and lac was normal in all but one animals.…”
Section: Discussionsupporting
confidence: 84%
“…Potent opioids result in rapid induction times and therefore a reduced risk of capture myopathy and injury ( 6 , 7 ). However, they are associated with muscle rigidity, respiratory depression, hypertension, acidemia and hyperlactatemia ( 6 , 8 , 9 ). Azaperone is the most commonly added tranquilizer, but is reported to inhibit semen emission ( 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, the lower arterial oxygenation measured in black rhinoceroses during lateral compared to sternal recumbency is in line with previous reports in black rhinoceroses, white rhinoceroses and horses (Gleed & Dobson 1988 ; Radcliffe et al . 2014 ; Wenger et al . 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study demonstrated that black rhinoceroses immobilised with etorphine and azaperone experienced more severe hypoxaemia and lactic acidaemia during lateral compared to sternal recumbency (Radcliffe et al . 2014 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation